2022
DOI: 10.3390/su142013392
|View full text |Cite
|
Sign up to set email alerts
|

Crowding-Out Effect of Natural Resources on Domestic Investment: The Importance of Information Communication and Technology (ICT) and Control of Corruption in the Middle East and Central Asia

Abstract: Countries of the Middle East and Central Asia depend heavily on natural resources for their exports, income, and employment. This study is a preliminary investigation that explores the effect of natural resources on domestic investment in a sample of 12 highly resource-dependent countries in the Middle East and Central Asia from 2000 to 2019. The recently advanced cross-sectional dependent auto-regressive distributed lag (CS-ARDL) model and panel quantile regression are employed. The results validate the accel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Accelerator theory states that investments are undertaken to satisfy a desired level of demand. An increase in demand for the company's products is met by the company increasing its production through more investments, and accordingly, income becomes higher (Abbas et al, 2022;Olakojo and King, 2023). Investment here is proportional to output, so the expected output is the major determining factor of investment behavior.…”
Section: Corporate Investment Decisionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accelerator theory states that investments are undertaken to satisfy a desired level of demand. An increase in demand for the company's products is met by the company increasing its production through more investments, and accordingly, income becomes higher (Abbas et al, 2022;Olakojo and King, 2023). Investment here is proportional to output, so the expected output is the major determining factor of investment behavior.…”
Section: Corporate Investment Decisionmentioning
confidence: 99%
“…According to Saquido (2003), institutional quality is important because strong governance is linked with more economic growth and development, thus increasing the opportunity to attract further investment. The economy’s strength and continuous expansion demand stimulating investment activities that ensure continuous money circulation, increased earnings and economic recovery (Dempsey, 2003; Abbas et al , 2022). In turn, Ajide (2017) and Sayed and Petkar (2022) indicated that the expansion of GNP and the confidence it inspires imply an increase in investment prospects and should therefore raise the level of investment.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…Achieving well-being at each level is determined by the level of social capital, in particular, the development of effective education, and the achievement of a high level of quality of life for the population as a whole. Moreover, if at the level of global discussion there is a pool of works devoted to welfare issues in the framework of achieving sustainable development goals [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], as well as the impact of ESG factors on the financial performance of regions and industries [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], then in Russia research is fragmented. Issues of the green economy from the perspective of environmental priorities and the transition to a sustainable measurement of economic growth, social responsibility of business, issues of responsible financing, development of calculation methods and empirical assessment of the impact are worked out in the works of Annenskaya N.E., Bataeva B.S., Blagov Yu.E., Bobylev S.N., Vostrikova E.O., Ivashkovskaya I.V., Makeeva E.Yu., Meshkova A.P., Pilyugina A.V., Tkachenko I.N.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in the context of research, digitalization is considered as one of the factors influencing the sustainable development of the global economy, including welfare. Similar to ESG factors, digitalization creates paradoxical effects on well-being [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…In our globally interconnected economies, shocks inside a part of the economic system or from outside can transform into extreme worldwide financial slumps through the entire system, contributing to developing disparities across economies. On 30 January 2020, the World Health Organization (WHO) released COVID-19's first global warning; further, the organization stated COVID-19 was a global pandemic on 11 March 2020, as the figure of confirmed cases escalated globally [1]. The current COVID-19 widespread has led to the most severe financial downturn in about a century, putting people's well-being at risk, hampering economic growth, and jeopardizing their employment.…”
Section: Introductionmentioning
confidence: 99%